Reduction of Sclerotinia sclerotiorum initial inoculum in soybean grown after the use of the Santa Fé system - Görgen, Claudia Adriana; Civardi, Ederson Antônio; Ragagnin, Vilmar Antônio; da Silveira Neto, Américo Nunes; Carneiro, Luciana Celeste; Lobo Junior, Murillo (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the effectiveness of Santa Fé system on reduction of the initial inoculum of Sclerotinia sclerotiorum, the causal agent of white mold in soybean. The experiment was carried out in Jataí, GO, Brazil, during 2007/2008, 2008/2009 and 2009/2010 growing seasons, in a commercial field naturally infested with the pathogen. Evaluations were done for number of sclerodia germinated on the soil surface, and for the pathogen number of apothecia and stipes. The experimental design was a randomized block, in a 2x4 factorial arrangement with four replicates. The treatments comprised the Santa Fé system use (maize + Urochloa ruziziensis), and maize as a single crop, both sown at the "safrinha" period (March 2008 and 2009). Furthermore, four evaluation dates of sclerotium germination and apothecium and stipe production were studied. The Santa Fé system increased the proportion of sclerotia smaller than 2 mm, considered as of lower infectivity, and promoted the reduction of the initial inoculum through the germination of sclerotia and the development of apothecia between the soybean growing seasons, what reduced the germinated sclerotia and the number of apothecia in the full flowering stage during soybean growing seasons. Santa Fé system can reduce the initial inoculum of S. sclerotiorum, and it may be used for the management of white mold in soybean.